Analysis of the Package Tour Consumption Behaviors of Families in Taiwan, 2009–2019 - Tzong-Shyuan Chen; Chi-Pei Ou Yang; Jui-Yuan Chu (Engineering Proceedings)
Destination platforms provide travel information and cheaper travel products, thus increasing the number of individual travelers. Therefore, travel agencies need to understand consumer behaviors toward family package tours and maintain and create new business opportunities. Using the cohort analysis method, we studied three variables in the time dimension: age, period, and cohort effects. A two-part model was combined to construct a model of family package tours in Taiwan, using data from the “Survey of Family Income and Expenditure in Taiwan” covering the period from 2009 to 2019. The results show that there were two peak periods when customers chose package tours: when the head of the household was between 46 and 50 years of age and between 66 and 70 years of age. A younger head of household had a higher willingness for such tours than an older one. The highest selection rate for these tours occurred in 2013, and then, it decreased gradually. Families with a head of household aged between 71 and 75 years had the highest expenditure on family package tours.